2022
DOI: 10.26832/24566632.2022.0702018
|View full text |Cite
|
Sign up to set email alerts
|

Understanding farmers’ knowledge, attitudes and practices of pesticide use in Nepal: synthesis of a systematic literature review

Abstract: Literature suggests a deeper understanding of farmers’ knowledge, attitude and practice (KAP) of pesticide use in agriculture, especially in developing countries, to identify interventions to reduce pesticide use in agriculture. In this paper, we thus performed a systematic review of literature on KAP of farmers on chemical pesticide use in Nepal through a systematic literature search on Scopus web repository published between 2000 and 2021. We got 114 publications initially, and with a well-defined inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(93 reference statements)
0
3
1
Order By: Relevance
“…This is crucial for minimising health risks associated with chemical exposure. In contrast to the results presented by Atreya et al (2022), which indicated that the utilisation of gloves and goggles is not frequently observed among farmers, our findings reveal a different pattern. The mean for "I carefully read and understand the instructions, warnings, and safety precautions provided on agrochemical labels" (mean = 3.88, SD = 0.73) suggests that farmers agree with carefully reading and understanding the instructions, warnings, and safety precautions provided on agrochemical labels.…”
Section: Safety Compliance Measures Observed By Cocoa Farmerscontrasting
confidence: 99%
“…This is crucial for minimising health risks associated with chemical exposure. In contrast to the results presented by Atreya et al (2022), which indicated that the utilisation of gloves and goggles is not frequently observed among farmers, our findings reveal a different pattern. The mean for "I carefully read and understand the instructions, warnings, and safety precautions provided on agrochemical labels" (mean = 3.88, SD = 0.73) suggests that farmers agree with carefully reading and understanding the instructions, warnings, and safety precautions provided on agrochemical labels.…”
Section: Safety Compliance Measures Observed By Cocoa Farmerscontrasting
confidence: 99%
“…Our findings found that farmers with higher perceptive scores had a lower prevalence of all symptoms, and farmers with higher practice scores had a lower prevalence of skin symptoms. Previous studies revealed that lack of knowledge, attitude, and practice (KAP) of pesticide use is a major cause of pesticide misuse and poisoning symptom related to pesticide exposure ( 13 , 52 , 53 ). Additionally, our findings show that the least farmers’practices regarding safe pesticide were as follows: wear rubber apron while applying pesticides; do not keep remaining pesticides that have been mixed for use later; do not mix pesticides in a cocktail; choose less toxic pesticides for killing pests; and wear goggles while applying pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pictograms and color codes on pesticide label are intended to be readily understood by farmers with varying languages and literacy levels, previous studies conducted in several countries showed a varied understanding of the massage on pesticide labels ( 55 , 56 ). Lack of training is also a major cause of pesticide misuse ( 53 ). Therefore, continuous training regarding safe pesticide use by using practical methods is urgently need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation